Challenges in measuring dorsal comminution in distal radius fractures using plain radiography: an observational study - Chae, SangHoon; Lee, Jae-Hoo; Kim, Dong-Suk; Lee, Hyun Il (Archives of Hand and Microsurgery, 2025)
Purpose: Dorsal comminution is widely accepted as a prognostic factor for reduction loss in the nonoperative treatment of distal radius fractures. However, the reliability of measuring dorsal comminution in simple radiographs has not been adequately studied. This study investigated the reliability of dorsal comminution measurements from simple radiographs, based on inter- and intra-rater reliability indices.Methods: We included 40 patients with distal radius fractures who underwent operative treatment from March 2016 to March 2017. We established three definitions for dorsal comminution: first, the rater’s subjective judgment; second, the presence of a free-floating piece of dorsal cortex; and third, the presence of a dorsal cortical defect of 5 mm or greater. Reliability was measured using Fleiss’ or Cohen’s kappa.Results: Based on Cohen’s kappa values, the intra-rater reliability of dorsal comminution assessment demonstrated fair to good agreement. In contrast, inter-rater reliability was generally poor to fair, and subgroup analysis by rater experience revealed poor agreement among less experienced surgeons.Conclusion: The radiological predictors of dorsal comminution exhibited overall low reliability, limiting their usefulness in predicting reduction loss in distal radius fractures. A more precise definition of dorsal comminution is necessary, and additional methods, such as computed tomography and artificial intelligence, should be considered to increase reliability.